The Effect of Nanoparticles Composition on Tensile and Thermal Properties of Polystyrene Reinforced with Graphene Nanoplatelets - H, Baharom M.; Z, Mat Desa M.S.; I, Izhab; M, Yusop; Z, Kasnan N.; F, Ab Ghani N. (International Journal of Engineering and Technology, 2018)
This study presents the reinforcement effect of graphene nanoplatelets (GNP) on tensile and thermal properties of polystyrene/graphene nanoplatelets (PS/GNP) nanocomposites. The PLA/GNP nanocomposites were prepared by melt-blending method with the GNP contents varied at 0.5, 1.0, and 1.5 wt %. The tensile properties of PS/GNP nanocomposites were analysed by using universal testing machine, the thermal properties were investigated by thermal gravimetric analysis (TGA), and thermal conductivity analysis, while the morphology were characterized by Transmission Electron Microscopy (TEM) and X-Ray Diffraction (XRD) measurement.Â  Steady improvement of tensile strength and Youngâ€™s Modulus was observed as the composition of GNP increased. The study also showed that the thermal stability and thermal conductivity of PS/GNP nanocomposites increase with increasing content of GNP. This study indicates strong influence of GNP contents on reinforcement effect and thermal properties of PS/GNP nanocomposites.